Regenerative Agriculture Practices And Their Effect On Soil Health And Agribusiness Profitability In Indonesian Farming Systems - Miyarnis Miyarnis; Lutfi Henderlan Harahap; Yelfi Yana Linda Br Jabat (International Journal of Science and Environment (IJSE), 2026)
Global agriculture faces significant threats from climate change and soil degradation, with approximately 66.49% of Indonesian agricultural land currently categorized as unsustainable. This study analyzes the impact of regenerative agriculture practices on soil health indicators and agribusiness profitability within Indonesian farming systems. Using a mixed-methods research design, data were collected from smallholder farmers in Deli Serdang Regency, North Sumatra Province, Indonesia, comparing those adopting regenerative techniques against those using conventional methods. The study concludes that regenerative agriculture serves as a viable win-win strategy for Indonesian smallholders, offering a pathway to restore degraded ecosystems while enhancing economic resilience through cost-efficiency. Policymakers are encouraged to integrate these practices into national development strategies to support Indonesia’s 2045 food self-sufficiency targets.